2011
DOI: 10.1261/rna.02962911
|View full text |Cite
|
Sign up to set email alerts
|

Plant-type mitochondrial RNA editing in the protist Naegleria gruberi: FIGURE 1.

Abstract: RNA editing converts hundreds of cytidines into uridines in plant mitochondrial and chloroplast transcripts. Recognition of the RNA editing sites in the organelle transcriptomes requires numerous specific, nuclear-encoded RNA-binding pentatricopeptide repeat (PPR) proteins with characteristic carboxy-terminal protein domain extensions (E/DYW) previously thought to be unique to plants. However, a small gene family of such plant-like PPR proteins of the DYW-type was recently discovered in the genome of the proti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…The DYW consensus contains the cytidine deaminase signature HxE (x)nCxxC (Salone et al, 2007). In addition, the phylogenetic distribution of the DYW domain appears to exactly match the phylogenetic distribution of plant organellar RNA editing (Salone et al, 2007;Knoop, 2011;Rüdinger et al, 2011). These results supported the hypothesis that the DYW domain might contain the catalytic activity for editing in plant organelles (Salone et al, (A) Alignment of the DYW1 sequence with the DYW domain consensus .…”
Section: Introductionsupporting
confidence: 60%
“…The DYW consensus contains the cytidine deaminase signature HxE (x)nCxxC (Salone et al, 2007). In addition, the phylogenetic distribution of the DYW domain appears to exactly match the phylogenetic distribution of plant organellar RNA editing (Salone et al, 2007;Knoop, 2011;Rüdinger et al, 2011). These results supported the hypothesis that the DYW domain might contain the catalytic activity for editing in plant organelles (Salone et al, (A) Alignment of the DYW1 sequence with the DYW domain consensus .…”
Section: Introductionsupporting
confidence: 60%
“…Among several other features, the recently developed PREPACT allows automatic prediction of RNA editing sites in multiple sequence alignments or in full organelle genomes (Lenz et al 2010). The latter option has recently been used successfully to identify candidate RNA editing sites even in the mtDNA of a phylogenetic distant protist, which could subsequently be confirmed Rüdinger et al 2011a). However, RNA editing prediction with this strategy frequently proves to be too sensitive and identifies false positive candidate sites when based on individual reference sequences alone.…”
Section: Amending Prepact For Stringent Editing Site Predictionsmentioning
confidence: 97%
“…The DYW domain is known to have zinc binding motifs (HXE and CXXC) (25), and analogous zinc-coordinating residues are conserved in nucleotide deaminases (26 -29). Phylogenetic analyses have shown that the distribution of PPR proteins with the DYW domain coincides with the distribution of C-to-U editing in land plants (25), in the protist, Naegleria gruberi (30,31), and possibly also in diverse lower eukaryotes such as Acanthamoeba, Physarum, Nitella, and rotifers (32). A bioinformatics analysis of the deaminase superfamily has shown that the C-terminal region exhibits structural characteristics of a deaminase domain and places the DYW deaminase domain in the deaminases superfamily (27).…”
Section: Pentatricopeptide Repeat (Ppr)mentioning
confidence: 98%